A woman as seen by a man in modern Russian chanson - Berestnev G.; Yevstafyeva M. (Слово.ру: балтийский акцент, 2013)
This article reconstructs the portrait features of a woman as presented in ’female’ modern Russian chanson. The authors emphasise the woman’s original self-perception as opposed to the way she is presented in chanson by a man. Such original features include a greater number of details in the ‘self-portrait’, orientation towards the male psychological models of perceiving reality, and the use of an image of an ageing woman. Love and at the same time freedom are presented as a woman’s basic life values, which is indicative of changes in the female gender perception in the modern Russian society.